AD‐causing variants that affect PSEN1 transmembrane domains are associated with faster neurodegeneration and cognitive decline compared to those affecting cytoplasmic domains. (20th December 2022) - Schultz, Stephanie A.; Allegri, Ricardo Francisco; Schultz, Aaron P.; Goate, Alison; Levey, Allan I.; Fagan, Anne M.; Hanseeuw, Bernard J; Koeppe, Robert A.; Gordon, Brian A.; Cruchaga, Carlos; Karch, Celeste M.; Chen, Charles D.; et al.
Abstract: Background: Rates of cognitive and biomarker change in Autosomal Dominant Alzheimer disease (ADAD) vary substantially across individuals. Prior cross‐sectional work suggests that the location of the pathogenic variant within PSEN1, specifically whether the underlying variant affects transmembrane (TM) or cytoplasmic (CY) domains in PSEN1, may be a key determinant in these differential rates of progression. Here we use longitudinal data from the Dominantly Inherited Alzheimer Network observational study (DIAN‐Obs) to examine whether variants affecting TM versus CY domains in PSEN1 have differential rates of change in key cognitive and neurodegenerative markers, and whether these differences are relevant to ADAD clinical trials. Methods: Using longitudinal clinical, cognitive, and MRI data from PSEN1 pathogenic variant carriers [TM group N=76 and CY group N=44; Table 1 ], we assessed rates of change in Mini‐Mental State Exam (MMSE), Clinical Dementia Rating ® Sum of Boxes (CDR ® ‐SOB), and hippocampal volume (HV) using linear mixed effects models accounting for disease stage (estimated years to symptom onset [EYO]). We further assessed how PSEN1 mutation location (TM versus CY) impacts sample size and detectable effect size in a potential ADAD clinical trial (modeled as a 4‐year trial with annual assessments; 80% power; α = 0.05). Results: PSEN1 TM and PSEN1 CY groups did not differ on baseline age, EYO, or CDR ® . The PSEN1 TM group had significantly greater rates of change on MMSE (B[SE] = ‐0.42[0.1], p=0.002), CDR ® ‐SOB (B[SE] = 0.23[0.1], p=0.001), and HV atrophy (B[SE] = ‐58.93[14.3], p=0.0006 compared to the PSEN1 CY group (Fig.1 ). Consistent with these differential rates of change, power analyses indicated the required sample size to detect a 30% treatment effect on MMSE or HV would be reduced by 59.6% for MMSE and 91.0% for HV for a trial population comprised of PSEN1 TM versus CY carriers (Fig.2 ). Conclusions: Individuals who had a variant affecting the transmembrane domains of PSEN1 had greater rates of cognitive decline and neurodegeneration compared to those with variants affecting cytoplasmic domains. In addition to having implications for ADAD pathophysiology, these results suggest that incorporating information regarding the location of PSEN1 variants may be beneficial in analyzing and designing stratification approaches for ADAD trials.